Assessment of fetal lung maturity by ultrasound: an update - Albinagorta Olórtegui, Roberto (2016)
Respiratory distress syndrome (RDS) of the newborn remains a major cause of morbidity and mortality in preterm infants. Although the latest scientific evidence questions the utility of fetal lung maturity testing to determine the most suitable moment for delivery in certain obstetrical complications, there is a set of relative indications in which a non-invasive test can find application. The aim of this paper is to review studies published on the use of ultrasound as a method to predict neonatal respiratory morbidity, using both Doppler evaluation of the pulmonary artery and ultrasound quantitative analysis of fetal lung texture.